PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH BERUPA PRODUK OLAHAN BERBASIS JAGUNG DI DESA PABUARAN - Widodo Hami; Hendri Setyaji; Hamidah (Al-Nizam: Indonesian Journal of Research and Community Service, 2023)
ABSTRACT Poverty is a condition where a person cannot fulfill his basic needs in order to lead a more dignified life. Therefore, poverty must be overcome, because if it is not overcome it will be able to interfere with national development. Through the development of a strategy for micro, small and medium enterprises in Pabuaran Village as an effort to fight poverty, one of them is the innovation of making coffee made from corn. Yellow corn is the main commodity in the agriculture of Pabuaran Village. This corn can usually only be processed for animal feed needs because it tastes bland. However, with the right method, technique and formulation, it can now be processed into post-harvest processed products such as corn coffee. Corn coffee innovation is made to change the selling value of corn to be higher so that it can help the economy of the Pabuaran village community. The purpose of writing this journal is to demonstrate the right methods, techniques, and formulations to process innovation the corn into corn coffee with quality that is acceptable to the public. This research is a collaboration between LP2M UIN K.H Abdurrahman Wahid carried out by KKN 53 in 2022 and the Pabuaran Village Government, Bantarbolang District, Pemalang. Keywords: Poverty, Business Development, Corn Coffee